INTERACTIVE READING USING AUTHENTIC MATERIALS IN AN EFL CONTEXT (NOBEL: Journal of Literature and Language Teaching, 2013)
This paper discusses the practical strategies of how to teach reading skills communicatively using authentic materials in an English as a foreign language context. Reading is approached as an interactive process between the readers‟ mind and the text. It is not merely a receptive activity but it is a process whereby readers create imaginations and anticipate ideas which might come up from the linguistic forms of the text. Throughout the reading process, readers construct ideas by synergizing the ideas of their minds and the signs conveyed by the text. Hence, comprehension is more efficient. In order to comply with such a process, learners are facilitated maximally through the activation of their background knowledge and the provision of linguistic and conceptual hints which are conducted by teachers in a pre-reading phase. To develop the linguistic skill and affirm the comprehension, furthermore, the ideas that have been constructed throughout the whilst-reading step are, then, used as materials to conduct the post reading activities.Key words: interactive reading approach, authentic materials, three-phase techniques